The Promotion Strategy for Artworks by Artist A.C. Andre Tanama - Galuh Wardani; Latifa Nilamsari; Siti Malihatussa'diyyah; Yudis Ritmana Vibra (Institut Seni Indonesia Yogyakarta, 2023)
A.C. Andre Tanama is an artist and lecturer at the Indonesian Institute of the Arts in Yogyakarta. He has had several solo exhibitions and his work has captivated many people. One of them was the artwork of A.C. Andre Tanama, which at that time was exhibited at the R.J. Katamsi Gallery and managed to captivate Dr. Oei Hong Djien was collected by the collector from Magelang, Central Java. Since the beginning of his career as an artist, he has published and promoted works using publication media such as website, Instagram, and Facebook, and also through his relationships with other artists and art collectors. In addition to using online media, he has a unique way of publishing and promoting his work through books and catalogs of his works. Throughout his career as an artist, Andre has three distinctive characters who fill his works: Wayang Monyong, Gwen Silent, and Agathos. Through these three distinctive characters, the artist tries to represent what the artist feels and experiences. Where several messages/signs in those artworks can be felt or captured by the audience. The focus of this research is to find out what are important things related to the promotion of the works of the artist A.C. Andre Tanama. Data collection techniques in this study were carried out by observation, interviews, and documentation methods. The results of this study are expected to be able to contribute as a reference to find out what are important things related to the promotion of works of art in the style of A.C. Andre Tanama